2018
DOI: 10.1016/j.neuroscience.2018.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Masking Differentially Affects Envelope-following Responses in Young and Aged Animals

Abstract: Age-related hearing decline typically includes threshold shifts as well as reduced wave I auditory brainstem response (ABR) amplitudes due to cochlear synaptopathy/neuropathy, which may compromise precise coding of suprathreshold speech envelopes. This is supported by findings with older listeners, who have difficulties in envelope and speech processing, especially in noise. However, separating the effects of threshold elevation, synaptopathy, and degradation by noise on physiological representations may be di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 88 publications
1
12
0
Order By: Relevance
“…Recent animal neurophysiology studies have demonstrated that an FFR similar to that of humans can be recorded in awake monkeys 83 , confirming previous demonstrated analogs between humans and anesthetized non-human animals 37,38,84,85 . Awake animal preparations could be particularly enlightening because of the possibility of recording simultaneously from multiple sites in behaving animals.…”
Section: Evidence For Multiple Sources In Human Scalp-recorded Ffrsupporting
confidence: 80%
See 1 more Smart Citation
“…Recent animal neurophysiology studies have demonstrated that an FFR similar to that of humans can be recorded in awake monkeys 83 , confirming previous demonstrated analogs between humans and anesthetized non-human animals 37,38,84,85 . Awake animal preparations could be particularly enlightening because of the possibility of recording simultaneously from multiple sites in behaving animals.…”
Section: Evidence For Multiple Sources In Human Scalp-recorded Ffrsupporting
confidence: 80%
“…The FFR is useful to address questions concerning impaired auditory processing in populations with impaired cochlear function 2326 , and in neurodevelopmental speech and language disorders 2732 or autism 33,34 . It can also be used to study maturational 35,36 and aging-related changes 37,38 , sex differences in auditory functions 39 , and improvement caused by interventions 15,4042 . More broadly, the FFR can provide an index of neurological health, for instance, in populations with acquired neurological disorders (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This dichotomy is ripe for further study since the Hz and 45 Hz modulations represent different temporal processing regimes and components of speech (Rosen 1992). In studies on age-related auditory nerve deficit models and AM-in-noise responses in aged animals, decreased sensitivities to lower SNRs in AM-in-noise in damaged auditory systems have been observed (Parthasarathy et al 2016;Lai et al 2017;Lai and Bartlett 2018). This phenomenon could partly explain the changes seen in 45 Hz AMF.…”
Section: Amplitude Modulation Efrsmentioning
confidence: 94%
“…For AM in Noise stimuli, the same EFRs were used alongside a 71 Hz sinusoidally AM masker of the same length and onset, with Gaussian noise as the carrier, similar to Lai and Bartlett (Lai and Bartlett, 2018). Noise AM maskers were presented at sound levels of 20dB SNR and 0SNR to the sound level of target AM.…”
Section: Efrsmentioning
confidence: 99%
“…Affects balance system of squid [113] 9 Physiological Stress [114] 10 Irritation [115] 11 Difficulty in communication [116] 12 Nervousness [117] Animals also suffer human like disabilities like hearing loss, loss in responsiveness, dizziness and disturbance [93]. Traffic noise reduced foraging efficiency in most bats [94].…”
Section: References Effects Referencesmentioning
confidence: 99%